2008
DOI: 10.2174/1874095200802010083
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for the Synthesis of 1,5-benzodiazepin-2-one

Abstract: New 3-hydroxy-1,5-benzodiazepin-2-ones were synthesized through condensation between ophenylenediamines with glycidic ester. Alkylation and oxidation of some of the obtained compounds were also explored in different conditions yielding various oxidized and alkylated benzodiazepines. The structural elucidation of the synthesized compounds was achieved by MS, NMR spectroscopy and also through X-ray diffraction analysis. The glycidic ester was thus shown to be an interesting synthon in the synthesis of new 1,5-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Solid-phase synthetic strategies have been applied to prepare 4,5-dihydro-1 H -[1,5]­benzodiazepin-2-one derivatives. , Xiaoxia Wang and co-workers have demonstrated that o -phenylenediamine reacted with N -cinnamoylbenzotriazoles via 1,4-addition to afford 1,3,4,5-tetrahydro-1,5-benzodiazepin-2-ones . In addition, several other groups also reported their studies on this subject . However, to the best of our knowledge, only one example of enantioselective synthesis of these compounds has been described.…”
mentioning
confidence: 99%
“…Solid-phase synthetic strategies have been applied to prepare 4,5-dihydro-1 H -[1,5]­benzodiazepin-2-one derivatives. , Xiaoxia Wang and co-workers have demonstrated that o -phenylenediamine reacted with N -cinnamoylbenzotriazoles via 1,4-addition to afford 1,3,4,5-tetrahydro-1,5-benzodiazepin-2-ones . In addition, several other groups also reported their studies on this subject . However, to the best of our knowledge, only one example of enantioselective synthesis of these compounds has been described.…”
mentioning
confidence: 99%